Development affordable ferrocement roof cover using sustainable building material - Umar, Hj. Kassim (Real Estate and Housing Developers’ Association (REHDA) Federal Territories, 2011)
The International Conference on World Class Sustainable Cities 2009 organized by Real Estate and Housing Developers’ Association (REHDA), Federal Territories, the Malaysian Institue of Planners (MIP) and the Malaysian Institute of Architects (PAM), 24th March 2009 at Renaissance Hotel, Kuala Lumpur, Malaysia.